Math Anxiety: The Relationship Between Parenting Style and Math Self-Efficacy - Macmull, Moran S.; Ashkenazi, Sarit (Frontiers in Psychology, 2019)
The goal of the current study is to examine the direct and indirect influences of parenting styles, math self-efficacy, and the participants’ sex on math anxiety. The research population (N = 204) included randomly selected participants, whose native language is Hebrew and were born in Israel. The participants were surveyed about four measures that served as the research tools. They answered questions about demographics, math anxiety, and the parenting style of the child’s mother and about math self-efficacy. The research data concluded that there were strong correlations between the authoritarian parenting style and math anxiety. The authoritative parenting style had both a direct positive correlation and an indirect negative correlation on math anxiety. This is in contrast to the permissive parenting style which was exclusively found to have a small positive correlation on math anxiety. The participant’s sex had both direct and indirect influences on math anxiety. Math anxiety levels, as well as the negative effects of self-efficacy on the level of math anxiety, were higher in females compared to males. These findings are relevant when considering methods of diagnosis and intervention surrounding math anxiety.